Experiments with sodium bicarbonate for the control of feed lot death losses. Sorghum grain and roughage combinations for fattening lambs. - Cox, R.F.; Erhart, A.B. (Kansas Agricultural Experiment Station, 2012)
Experiments in the use of bicarbonate of soda for the control of death losses in the feedlot were begun last year. Two small scale tests indicated that it was highly beneficial. In this years experiments, four lots of lambs were used to give further tests of the value of sodium bicarbonate in the feed and in the water.
Keywords: Lamb; Bicarbonate; Feedlot; Sorghum grain; Roughage